Bone mineral density and bone metabolic markers' status in children with neurofibromatosis type 1 - Poyrazoglu, Hatice Gamze; Bas, Veysel Nijat; Arslan, Alev; Bastug, Funda; Canpolat, Mehmet; Per, Huseyin; Kumandas, Sefer (Walter de Gruyter Gmbh, 2017)
Background: Neurofibromatosis type 1 (NF1) is a multisystem disorder characterized by progressive manifestations, which is inherited in an autosomal dominant manner. The majority of patients with NF1 experience a diffuse, significant reduction in bone mass over time, with osteoporosis, osteopenia in the absence of severe scoliosis, or gross bone deformities. This study aimed to determine the bone mineral density (BMD) status, evaluate bone metabolism, and to determine the relevant factors in children with NF1. Methods: The study population included 33 pediatric NF1 patients (20 males and 13 females). Bone metabolic markers, such as total calcium, phosphorus, magnesium, alkaline phosphatase, parathyroid hormone, and 25-OH vitamin D, the urinary calcium/creatine ratio were measured. In addition, BMD was measured at both the lumbar spine (LS) and the femoral neck in all the patients. Results: All the patients had a low 25-OH vitamin D level, but it was significantly lower in the females than in the males (p < 0.009). Overall, 18.2% of the patients had skeletal abnormalities. The lumbar Z-score was <= 2 in 21.2% of the patients, whereas the femoral neck Z-score was <= 2 in 9.1%. The urinary calcium/creatine ratio was significantly higher in the female than in the male patients (p < 0.027). In all, six patients had skeletal abnormalities. Conclusions: It is widely known that bone mineral metabolism markers and BMD are significantly affected in NF1 patients; however, the present study did not identify any effective parameters that could be used to predict skeletal abnormalities, or diagnose early osteoporosis and osteopenia in pediatric NF1 patients.
Keywords: bone mineral density; bone mineral markers; children; neurofibromatosis type-1; osteoporosis